(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article discusses in detail the features of the plot of children’s prose, methods of image formation and ideological and artistic skill.